2008
DOI: 10.1177/107769900808500305
|View full text |Cite
|
Sign up to set email alerts
|

Access Attitudes: A Social Learning Approach to Examining Community Engagement and Support for Press Access to Government Records

Abstract: This survey-based study examines public attitudes toward press access to government records, deriving a political model predicting support for freedom of information based on social learning theory and testing whether support for press access is best explained by societal power, media importance, or political attitudes. Findings indicate that support is tied most closely to political attitudes such that the strongest predictors are community engagement and support for press rights, regardless of age, income, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 1 publication
0
15
1
Order By: Relevance
“…Even more widely used among journalists and journalism scholars is an alternative approach to engagement in terms of community connection or participation (Mersey, 2009a and2009b;Cuillier, 2008;Kwak, Shah, & Holbert, 2004;Kwak, Williams, Wang, & Lee, 2005;McLeod, Kosicki, & McLeod, 2002;McLeod, Scheufele, & Moy, 1999;Moy & Scheufele, 2000;Moy, Scheufele, & Holbert, 1999;Norris, 1996;Rothenbuhler, Mullen, DeLaurell, & Ryu, 1996;Shah, 1998;Shah, McLeod, & Yoon, 2001;Shah, Schmierbach, Hawkins, Espino, & Donovan, 2002;Stamm, Emig, & Hesse, 1997). We will call this the "civic experience."…”
Section: Media Engagement and Experiencesmentioning
confidence: 95%
“…Even more widely used among journalists and journalism scholars is an alternative approach to engagement in terms of community connection or participation (Mersey, 2009a and2009b;Cuillier, 2008;Kwak, Shah, & Holbert, 2004;Kwak, Williams, Wang, & Lee, 2005;McLeod, Kosicki, & McLeod, 2002;McLeod, Scheufele, & Moy, 1999;Moy & Scheufele, 2000;Moy, Scheufele, & Holbert, 1999;Norris, 1996;Rothenbuhler, Mullen, DeLaurell, & Ryu, 1996;Shah, 1998;Shah, McLeod, & Yoon, 2001;Shah, Schmierbach, Hawkins, Espino, & Donovan, 2002;Stamm, Emig, & Hesse, 1997). We will call this the "civic experience."…”
Section: Media Engagement and Experiencesmentioning
confidence: 95%
“…Another important area of sociological research on the transparency process involves public opinion toward transparency. In a survey of a random sample of the U.S. population, Cuillier (2008) found that support for the press and its role in democracy is associated with higher levels of favorability toward granting access to public records. In another study relying on a random-sample survey of residents in the U.S. state of Washington, Cuillier and Pinkleton (2011) found that political liberalism, skepticism, and cynicism were strongly correlated with support for government transparency.…”
Section: Sociology Of Law In Mass Communicationmentioning
confidence: 99%
“…The first group of statements explores opinions toward government transparency in general. These statements are based on studies by Cuillier (2008;Cuillier & Pinkleton, 2011) that have explored attitudes toward transparency among the general public. In particular, statements seek to address the extent to which public records officers feel a duty toward transparency versus a duty toward protecting their agency through keeping records secret (see Table 2, below, for questions).…”
Section: Attitudes Toward Government Transparencymentioning
confidence: 99%
“…We excluded 179 articles at the final coding stage because they ultimately did not meet our eligibility criteria when the full‐length article was coded and discussed. A total of 68 articles contained quantified measures of stakeholder engagement and met our final criteria …”
Section: Flow Of Article Reviewmentioning
confidence: 99%